(untitled) (Journal of Hama University, 2026)
The research aimed to determine the readiness of private banks operating in the city of Lattakia for the digital transformation process, by studying the technical, human, security, legislative, and strategic requirements necessary to ensure the success of this process. The researcher relied on the descriptive analytical approach, and data were collected using a questionnaire distributed to (184) employees working in the banks under study, where the number of returned questionnaires valid for analysis reached (172) questionnaires, with a response rate of (93.47%). The results revealed a strong impact of technical, human, security, and strategic requirements on the success of digital transformation, highlighting the need to update banking laws to enhance the digital environment. The research also presented a set of recommendations, most notably: developing the technical infrastructure, improving employee training programs, enhancing cybersecurity, and updating legislation to support digital transformation in private banks, which will contribute to the development of a more efficient and innovative banking environment in Lattakia.